2002
DOI: 10.1016/s1076-6332(03)80517-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Human Airway Segmentation Methods for Clinical Virtual Bronchoscopy

Abstract: Rationale and Objectives. The segmentation of airways from CT images is a critical first step for numerous virtual bronchoscopic (VB) applications. Automatic or semiautomatic methods are necessary, since manual segmentation is prohibitively time consuming. The methods must be robust and operate within a reasonable time frame to be useful for clinical VB use. The authors developed an integrated airway segmentation system and demonstrated its effectiveness on a series of human images. Materials and Methods.The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 36 publications
0
72
0
4
Order By: Relevance
“…5 Region of Interest Selection: A three-dimensional airway reconstruction was used to choose a region of interest (ROI) in each lung segment (see later) at the two different lung volumes ( Fig 1 ). An automatic algorithm using a region-growing approach, based on the iterative algorithm proposed by Kiraly et al, 16 was developed to segment airway trees. The airways segmentation began by selecting a seed point in the trachea.…”
Section: Image Analysismentioning
confidence: 99%
“…5 Region of Interest Selection: A three-dimensional airway reconstruction was used to choose a region of interest (ROI) in each lung segment (see later) at the two different lung volumes ( Fig 1 ). An automatic algorithm using a region-growing approach, based on the iterative algorithm proposed by Kiraly et al, 16 was developed to segment airway trees. The airways segmentation began by selecting a seed point in the trachea.…”
Section: Image Analysismentioning
confidence: 99%
“…In this case a threshold limit is applied through the scans, where the segmenting region defined by image pixels has a value higher than or equal to a defined threshold value. Many segmentation algorithms exist (Kiraly et al, 2002;Pal and Pal, 1993) which have been adopted by commercial software such as Mimics (Materialise, 2008) and Amira (VisageImaging, 2008). An alternative is Matlab's Image Processing module (MathWorks, 2007) which provides useful functions to develop algorithms found in the literature (Beare, 2006;Kundu, 1990) or to develop custom algortihms.…”
Section: Computational Model Generationmentioning
confidence: 99%
“…Studies have described clinical applications of virtual endoscopy to visualize the inside of the bronchi, paranasal sinus, stomach, bladder, small intestine, pancreatic duct, bile duct, and spine (2,6,8,10,11,16,19,21,23,24). Shigematsu et al (20) reported the use of virtual intravascular MR endoscopy for aneurysms in three cases.…”
Section: Incesu L Et Al: Mr Endoscopy In Cerebral Aneurysmsmentioning
confidence: 99%
“…Studies have described clinical applications of virtual endoscopy to visualize the inside of the tracheobronchial tree, paranasal sinus, stomach, bladder, small intestine, pancreatic duct, bile duct, and spine (2,(6)(7)(8)10,11,16,19,21,23,24). Virtual endoscopy used for preoperative planning in neurosurgery for endoscopic third ventriculostomy, nasal cavity and paranasal sinus surgery, and virtual endoscopy visualization of the sphenoid sinus and important adjacent structures is valuable for training and the preoperative planning of endonasal transsphenoidal surgery (15).…”
Section: Incesu L Et Al: Mr Endoscopy In Cerebral Aneurysmsmentioning
confidence: 99%